People-Centric Skills - Goldberg, Danny (Ascent Audio, 2020)
Embark on a journey to further develop your career when you listen to People-Centric Skills: Interpersonal and Communication Skills for Financial Professionals, 2nd Edition. Business leaders consider employee communication skills and critical thinking abilities as essential elements for success. In their work, all professionals must communicate clearly and rely on their interpersonal skills to be successful. This second edition of People-Centric Skills shares the fictional story of Dalton Zimmer, executive coach and public speaker. Dalton, all the while juggling his business, kids, and social life, provides coaching and communication strategies for handling challenging situations faced by his clients. This insightful narrative will help you expand communication and soft skills as a CPA, auditor, financial planner, or other financial professional. As Generation Z is entering the work force, the communication gap between Z and Boomers or Generation X is widening significantly. New to the second edition, you'll find a discussion of communication between generations and how to bridge them as a financial professional.